PRACTICES OF PEACEKEEPING EDUCATION IN LATVIA AND ESTONIA - Olena Akilina; Alla Panchenko (Borys Grinchenko Kyiv Metropolitan University, 2023)
The article summarizes and critically analyses the experience of the Baltic countries in the field of peace education and outlines the best peace-making practices and peace-making trends in the light of modern Ukrainian realities. When implementing peace education, Ukraine should take into account the need to solve the following problems: recognition and respect for multiculturalism, involvement of local communities in education policy; reconciliation, struggle against injustice and the consequences of conflict. The research uses a systematic approach that allows considering the education of peace in the education system. In addition, a set of methods of scientific knowledge used in the humanities and social sciences is used, in particular, methods of analysis, synthesis, induction, deduction, analogy, and generalization. A significant part of the information base of the research was formed during the internship at the universities of Latvia and Estonia. Summarizing the results of our research, we can say that the following main events took place in the education of the Baltic countries, aimed at the implementation of effective practices in the field of peacemaking: development of training in peacekeeping skills at various educational levels; emphasis on transformational competences, social-emotional skills and paying attention to the metacognitive capabilities of education seekers; development of more effective interactive forms of training for education seekers; development of informal peace education